P702 Treatment decisions in older inflammatory bowel disease patients: Applying gut feeling in an evidence-based era? A qualitative study. (15th January 2020) - Waars, S; Asscher, V; Pieterse, A; van der Meulen-de Jong, A; Mooijaart, S; Maljaars, J
Abstract: Background: The population of older patients with inflammatory bowel diseases (IBD) is increasing. Treating older patients is challenging as they are characterised by heterogeneity in geriatric domains, such as functional, social or mental status. Although treatment guidelines do not distinguish between older and adult patients with IBD, several studies have found a difference in applied treatment strategies. It is unknown which considerations contribute to this. Therefore, we performed semi-structured interviews with IBD gastroenterologists and IBD nurses to assess a) which patient characteristics they consider and b) which treatment goals they pursue in older IBD patients, compared with adult IBD patients and c) what view they have on prescribing IBD medications in older IBD patients. Methods: IBD gastroenterologists and IBD nurses practicing throughout The Netherlands were asked to participate. Purposive sampling ensured a heterogenous population. Interviews took place in May or July 2019 were audio recorded and conducted face to face. Two researchers coded the verbatim transcripts independently. Codes and themes were obtained inductively and were finalised in consensus. Recruitment was stopped when no new information came out of three consecutive interviews. Results: Ten gastroenterologists and five IBD nurses were included: eight females, median age 43 years (34–61), median years of experience in IBD care, eight years (1–20), three working in an academic centre. Comorbidity and polypharmacy were most frequently mentioned as important patient characteristics in the choice of treatment of IBD in older patients. Only when asked specifically, participants mentioned characteristics of frailty, of which self-dependence, mobility, and cognitive impairment most often. However, applying 'a clinical view' or 'gut feeling' were frequently mentioned and none of the participants assessed frailty systematically. Therapy goals in older patients differed from those in adult patients: participants indicated to pursue clinical remission more often than endoscopic remission. Most participants stated to be reluctant to prescribe thiopurines. Other opinions about preferred medication differed remarkably, especially regarding low dose prednisone maintenance therapy. Conclusion: In the treatment of older IBD patients, attention is paid to comorbidity and polypharmacy, but geriatric characteristics, such as functional or cognitive impairment or frailty are barely taken into consideration. Clinicians put lower priority on pursuing endoscopic remission in older compared with younger patients. The large variation in clinicians' treatment preferences reflects a lack of evidence regarding treatment of older patients with IBD.